Effect of Preoperative Anti Tuberculosis Drug Administration Duration on Tuberculous Spondylitis Surgical Treatment Outcomes - Preodita Agradi; Nucki Nursjamsi Hidajat; Ahmad Ramdan (Faculty of Medicine, Universitas Padjadjaran, 2020)
Preoperative anti-tuberculosis (TB) drugs play a role in surgery of TB spondylitis patients to prevent transmission in the operating room, reduce inflammatory processes and prevent relapse. Currently, there is no study on effects of preoperative anti TB drugs administration duration on the spinal TB patients surgical outcome at Dr. Hasan Sadikin Hospital (RSHS). This study used retrospective method by analyzing medical record data of TB spondylitis patients operated at RSHS, January 2014–May 2018. Based on the preoperative TB drugs duration, patients were divided into 2 groups: preoperative TB drugs group <2 and 2–4 weeks. Data analyzed were identity, duration of preoperative TB drugs administration, preoperative neurologic grade, preoperative CRP and ESR level, and postoperative data at 2 month follow up consisted of neurologic grade, postoperative CRP and ESR levels. The 58 patients consisted of 25 males and 33 females, Kolmogorov-Smirnov test showed a significant difference (p<0.05) in postoperative neurologic grade between preoperative TB drugs administration <2 vs 2-4 weeks. Unpaired T-Test showed postoperative CRP and ESR levels were significant (p<0.05). Postoperative neurologic grade in the preoperative TB drugs <2 weeks group was better vs the 2–4 week group. Operative procedure is more important in TB spondylitis patients treatment compared to a prolonged preoperative TB drugs administration. Pengaruh Lama Pemberian Obat Anti Tuberkulosis Preoperatif Terhadap Hasil Pengobatan Spondilitis Tuberkulosis yang Mengalami Tindakan OperatifObat anti tuberkulosis (OAT) preoperatif memiliki peranan penting dalam pembedahan pasien spondilitis tuberkulosis sebagai pencegahan penularan di kamar operasi, menurunkan proses inflamasi, dan mencegah relaps. Sampai saat ini belum terdapat penelitian mengenai pengaruh lama pemberian OAT preoperatif terhadap hasil pembedahan pasien spondilitis tuberkulosis di Rumah Sakit Dr. Hasan Sadikin Bandung (RSHS). Penelitian ini menggunakan metode retrospektif dengan menganalisisa data rekam medis pasien spondilitis tuberkulosis yang dioperasi di RSHS periode Januari 2014–Mei 2018. Berdasar atas lama pemberian OAT preoperatif, sampel dibagi menjadi 2 kelompok, yaitu kelompok pemberian OAT preoperatif <2 dan 2–4 minggu. Data yang dianalisis berupa identitas, lama pemberian OAT preoperatif, tingkat neurologis preoperatif, kadar CRP dan LED preoperatif, dan data post-operatif saat follow up 2 bulan berupa tingkat neurologis, kadar CRP, dan kadar LED. Terdapat 58 pasien terdiri 25 laki-laki dan 33 perempuan, uji Kolmogorov-Smirnov menunjukkan bahwa terdapat perbedaan yang signifikan (p<0,05) pada tingkat neurologis post-operatif antara kelompok OAT <2 vs. 2–4 minggu. Uji-t tidak berpasangan memperlihatkan bahwa kadar CRP dan LED post-operatif ditemukan bermakna secara signifikan (p<0,05). Tingkat neurologis postoperatif pada kelompok pemberian OAT preoperatif <2 minggu lebih baik bila dibandingkan dengan kelompok 2–4 minggu. Tindakan operasi lebih berperan penting terhadap hasil pengobatan pasien spondilitis tuberkulosis jika dibanding dengan lama pemberian OAT preoperatif.